2010
DOI: 10.5032/jae.2010.02102
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Agriculture Teachers toward Including Students with Disabilities

Abstract: The inclusion of students with special needs in regular education classrooms has been required by federal law for more than three decades. However, much of the responsibility for successful accommodation of students with disabilities rests upon the shoulders of teachers. Previous research has indicated that successful inclusion of students with special needs is strongly influenced by the attitude of teachers involved. In this study, all secondary agriculture teachers in Utah were surveyed to determine their at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…At home, questionnaire and interview data indicated that parents needed to take a little more time with their children yet they had other duties to perform. Their responses were in line with an earlier finding by Bender (2008) and Giffing (2009) who noted that there is an additional expense, time and energy to care for the child with a special education need.…”
Section: Challenges Encountered By Parents Of Children With Special Esupporting
confidence: 88%
See 4 more Smart Citations
“…At home, questionnaire and interview data indicated that parents needed to take a little more time with their children yet they had other duties to perform. Their responses were in line with an earlier finding by Bender (2008) and Giffing (2009) who noted that there is an additional expense, time and energy to care for the child with a special education need.…”
Section: Challenges Encountered By Parents Of Children With Special Esupporting
confidence: 88%
“…Those who thought that inclusive education was good argued that the policy came as a relief since their children were admitted in neighbourhood schools. These observations were however, in line with what Turnbull et al (2010) and Giffing (2009) said when they advocated for inclusive education.…”
Section: Parents' Perceptions Towards the Implementation Of Inclusivesupporting
confidence: 85%
See 3 more Smart Citations